2003
DOI: 10.1210/en.2001-211282
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Is Involved in Apoptosis Induced by Serum Withdrawal and Fatty Acids in the β-Cell Line Ins-1

Abstract: The potential toxic effects of high extracellular concentrations of fatty acids were tested in beta(INS-1)-cells cultured in the absence of serum, a condition known to alter cell survival in various systems. This may in part mimic the situation in type 1 or 2 diabetes where beta-cells are already insulted by various stressful conditions, such as cytokines and oxidative stress. Serum removal caused, over a 36-h period, oxidative stress and an early impairment of mitochondrial function, as revealed by increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
2
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 44 publications
8
151
2
1
Order By: Relevance
“…The toxic actions of NEFA on beta cell function may be mediated by similar pathways; several lines of evidence point to this. Exposure to NEFA causes oxidative stress [76,125,127,[138][139][140][141] followed by apoptosis [142], and IL-1 potentiates NEFA toxicity [143]. Exogenous IL-1 or other toxic immune mediators from the islet endothelium [144][145][146][147] or from the circulation may act in concert with dietary fatty acids to damage beta cells, although the signalling pathways involved may differ in some respects.…”
Section: Immune Mechanisms In Diabetes Pathogenesis: Beta Cell Destrumentioning
confidence: 99%
“…The toxic actions of NEFA on beta cell function may be mediated by similar pathways; several lines of evidence point to this. Exposure to NEFA causes oxidative stress [76,125,127,[138][139][140][141] followed by apoptosis [142], and IL-1 potentiates NEFA toxicity [143]. Exogenous IL-1 or other toxic immune mediators from the islet endothelium [144][145][146][147] or from the circulation may act in concert with dietary fatty acids to damage beta cells, although the signalling pathways involved may differ in some respects.…”
Section: Immune Mechanisms In Diabetes Pathogenesis: Beta Cell Destrumentioning
confidence: 99%
“…Chronic exposure of ␤-cells to high levels of fatty acids, particularly saturated fatty acids, is associated with impaired glucose-stimulated insulin secretion and eventually ␤-cell death (22)(23)(24)(25)(26)(27)(28) (Fig. 4A), whereas the concentration of stearate (18:0) was significantly elevated (Fig.…”
Section: Plasma Lipid Composition Of Scd1mentioning
confidence: 99%
“…Hyperglycemia and islet fatty acid and cholesterol accumulation have been previously associated with impaired ␤-cell function and cell death (22,24,25,29,30,(41)(42)(43). Consistent with altered ␤-cell function, GLUT2 (Slc2a2), insulin (Ins2), insulin promoter factor 1 (Ipf1/ Pdx1), glucokinase (Gck), and insulin receptor substrate 2 (Irs2) were all dramatically (Ͼ90%; Table 2) downregulated in type B islets from Scd1 Ϫ/Ϫ leptin ob/ob mice.…”
Section: Scd1 Deficiency In Obese Micementioning
confidence: 99%
“…However, chronic hyperglycaemia causes beta cell dysfunction characterised by reduced insulin biosynthesis [6] and increased levels of apoptosis (glucotoxicity) [7,8,9,10,11]. Similarly, acute exposure to NEFA potentiates glucose-induced insulin secretion by beta cells [12], whereas prolonged exposure to high concentrations of NEFA triggers beta cell apoptosis (lipotoxicity) [13,14,15,16,17]. A recent study showed that protein kinase B (PKB) activation can rescue MIN6 cells from oleate cytotoxicity [18].…”
Section: Introductionmentioning
confidence: 99%